ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PILIHAN KARIR SISWA: PENDEKATAN KUALITATIF DALAM KONTEKS PENDIDIKAN MENENGAH ATAS - Tiara Rizki Utami (Educatus, 2024)
In recent years, many students have faced limitations in their career options, despite the critical importance of determining their future careers. This study aims to identify and analyze factors influencing students’ career choices at the high school level. The method employed is a qualitative approach through in-depth interviews, observation, and document analysis of three different students. The research findings indicate that several significant factors influence students’ career choices, including special talents and intelligence, career interests, personality, as well as family background and socio-economic status. These findings underscore the complexity of adolescents’ career decision-making processes, where both internal and external factors play crucial roles. Thus, it can be concluded that factors influencing students’ career choices stem from individuals’ internal factors and the influence of their family environment. The implications of this research highlight the importance of educational and familial support in assisting students in choosing careers that align with their potentials and interests.